Pengaruh Good Corporate Governance (GCG), Partisipasi Masyarakat, Kompetensi Aparat dan Pengawasan Aparat Terhadap Efektivitas Pengelolaan Dana Desa - Triutami, Yeni; Widarno, Bambang (Teewan Journal Solutions, 2025)
This study aims to examine the effect of Good Corporate Governance (GCG), Community Participation, Apparatus Competence and Apparatus Supervision on the Effectiveness of Village Fund Management. The object was carried out in the Village Government of Punung District, Pacitan. The type of data used is quantitative data. The data source used is primary data. The population in this study were all Village Apparatus in Punung District, Pacitan. The sample used in this study was the Village Head, Village Secretary, Village Treasurer, Head of Planning Affairs, Head of Welfare Section, Head of Service Section. The sampling technique was carried out using purposive sampling method and tested with SPSS 23 programme. The data collection method used was a questionnaire. The data analysis method used is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression analysis test, and hypothesis testing. The results of this study indicate that (1). Good Corporate Governance (GCG) has a significant positive effect on the Effectiveness of Village Fund Management (2). Community Participation has a significant positive effect on the Effectiveness of Village Fund Management (3). Apparatus Competence has a significant positive effect on the Effectiveness of Village Fund Management (4). Apparatus Supervision has a significant positive effect on the Effectiveness of Village Fund Management.